TINGKAT PENGETAHUAN MEMENGARUHI SIKAP REMAJA DALAM MELAKUKAN PENCEGAHAN KANKER SERVIKS - Retno Winarti, Junita Silitonga (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2020)
Cervical cancer is one of the most common cancers by women in Indonesia, prevention and early detection is important in the treatment of cervical cancer. The purpose of this research is to know the attitudes of teenagers in the prevention of cervical cancer and affect it factors. Cross-sectional research using consecutive sampling technique with 148 students Akper Manggala Husada. The data anlisisi is performed with multiple linear regression. The results showed that students of Akper Manggala Husada have a positive attitude in the prevention of cervical cancer, there is a significant relationship of knowledge of cervical cancer with an attitude in the prevention of the incidence of cervical cancer (r = 0,374), other factors influencing are age (r = 0,345), family support (r = 0,266,) belief in the prevention of cancer of Servisk (r = 0,281), and family income (r = 0,264). Knowledge is a contributing factor to the attitude of the prevention of cervical cancer for the effort to improve the understanding of cervical kangker is important to do.